Microlearning as a new method of teaching soft skills to university students - Romanenko, Yulia N.; Solodovnikova, Ekaterina; Maksimenko, Nadezhda (Frontiers in Education, 2023)
Soft skills are very important in the modern world, both for communications and planning daily life and, as both employers and students claim, for career and professional activities. The development of soft skills can occur independently, but there are opportunities to teach them, including at university. Different formats can be used for this, and one of them is microlearning, using a cell phone and the student's interaction with the teacher and the group on social networks and educational platforms. This format has been applied to two courses at ITMO University: study skills and emotional intelligence. An experiment was conducted, which showed that students who took the course in the microlearning format received the same amount of information and were able to apply it just as well as students who took the course in the classical learning format. Based on the successful use of such a format as microlearning and all its advantages described in the article, in the future it is proposed to form other courses using this learning format.